Automatic design of extrusion dies and calibration/cooling systems - Nóbrega, J. M. (2011)
FEDER via FCT, Fundação para a Ciência e Tecnologia, under the POCI 2010 (project POCI/EME/58657/2004) and Plurianual programs.